2018
DOI: 10.1002/jmv.24947
|View full text |Cite
|
Sign up to set email alerts
|

Beclabuvir in combination with asunaprevir and daclatasvir for hepatitis C virus genotype 1 infection: A systematic review and meta‐analysis

Abstract: Daclatasvir, asunaprevir (ASV), and beclabuvir (BCV) are direct-acting antivirals (DAAs) for patients with hepatitis C virus genotype 1 infection. This systematic review and meta-analysis investigating the efficacy and safety of this three-drug combination in HCV genotype 1 infection. Eleven electronic search engines were searched for relevant publications. Studies were screened for eligibility and data was extracted. The outcomes were pooled as event rate and risk ratio (RR). The protocol was registered in PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Beclabuvir is a non-nucleoside polymerase inhibitor that potentially inhibit nonstructural protein 5B (NS5B) of HCV [25]. Previous studies, including phase 3 clinical trials have suggested beclabuvir have a high response rate at post-treatment week [26,27]. Moreover, the pharmacokinetic, efficiency and tolerability were also reported very favorable [28].…”
Section: Discussionmentioning
confidence: 99%
“…Beclabuvir is a non-nucleoside polymerase inhibitor that potentially inhibit nonstructural protein 5B (NS5B) of HCV [25]. Previous studies, including phase 3 clinical trials have suggested beclabuvir have a high response rate at post-treatment week [26,27]. Moreover, the pharmacokinetic, efficiency and tolerability were also reported very favorable [28].…”
Section: Discussionmentioning
confidence: 99%
“…The licensing of 1 and 2 represented the first approval of a combination of DAAs for the treatment of HCV infection although the combination of 52 and the nucleoside-based HCV NS5B inhibitor prodrug sofosbuvir (53) was approved by the FDA in December of 2013 [86,87]. Extending the therapeutic utility of 1 and 2 to include the treatment of HCV GT-1a infections required the addition of a third agent, the NS5B inhibitor beclabuvir (3), which was ultimately developed as a fixed dose combination comprising of 200 mg of 1, 30 mg of 2, and 75 mg of 3 administered on a BID schedule for 12 weeks [88][89][90][91][92][93]. In an international phase III clinical study designated the UNITY 1 trial that was conducted in 415 patients infected with HCV GT-1 who were non-cirrhotic, 91% of the patients achieved SVR 12 .…”
Section: Clinical Studies With Asunaprevirmentioning
confidence: 99%
“…Broadening the utility of 1 and 54 to treat HCV GT-1a infections required the addition of a third agent, the allosteric RNA-dependent RNA polymerase inhibitor beclabuvir (56) which was developed as a fixed-dose combination comprising of 30 mg of 1, 200 mg of 54, and 75 mg of 56 administered as a BID regimen for 12 weeks [120][121][122][123][124][125][126]. In the UNITY 1 international study which was conducted in 415 non-cirrhotic patients with HCV GT-1 infection, 91% of the patients achieved SVR 12 .…”
Section: Clinical Trials With Daclatasvirmentioning
confidence: 99%